2012
DOI: 10.1002/jid.2859
|View full text |Cite
|
Sign up to set email alerts
|

Local Success in Encouraging Participatory Irrigation Management: Policy Lessons From Indonesia

Abstract: Despite decades of promotion, efforts to encourage participatory irrigation management often falter. Nowhere is this more true that on the island of Java, Indonesia where multiple programmes and millions of dollars have resulted in few effective water user associations. Even so, pockets of participatory success exist. We present findings from one locally developed water user association training programme found in Yogyakarta, Indonesia that has experienced relative success in encouraging farmer participation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…While in Model C, we did see a significantly positive effect from taking part in the recent training program , this effect disappears when paired with other measures of training. The positive result is heartening, in that it seems to support the idea that training can be beneficial (Ricks & Arif, 2012). Even so, the relationship between training and WUA activity is weaker than that found among other variables, and its direction was reversed in other models.…”
Section: (D) Findings and Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…While in Model C, we did see a significantly positive effect from taking part in the recent training program , this effect disappears when paired with other measures of training. The positive result is heartening, in that it seems to support the idea that training can be beneficial (Ricks & Arif, 2012). Even so, the relationship between training and WUA activity is weaker than that found among other variables, and its direction was reversed in other models.…”
Section: (D) Findings and Discussionsupporting
confidence: 42%
“…This evidenced either some degree of excellence in the training program or some special characteristic unique to Sleman's water user groups. Initial research had indicated that it was due to training efforts of the irrigation agency (Ricks & Arif, 2012). Thus, I developed the survey to better understand how the relationship between irrigation officials and farmers determined WUA activity.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…In districts that did not emphasize agriculture, irrigation officials were allowed to pursue their own bureaucratic interests (Ricks, ). Even so, some street‐level bureaucrats engaged in promoting farmer participation despite the lack of political pressure due to individual commitments (Ricks & Arif, ). In essence, the level of success was dependent on the incentives of local officials.…”
Section: Lessons From Pim Reforms In Practicementioning
confidence: 99%
“…() concluded that along with several other aspects, participatory irrigation is equally relevant for improving management of water in Khorezm, Uzbekistan. Ricks and Arif () and Suhardiman () have shown that in Indonesia, it is the sociopolitical aspect of irrigation management that is really challenging. Ghazouani et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hornidge et al (2011) concluded that along with several other aspects, participatory irrigation is equally relevant for improving management of water in Khorezm, Uzbekistan. Ricks and Arif (2012) and Suhardiman (2008) have shown that in Indonesia, it is the sociopolitical aspect of irrigation management that is really challenging. Ghazouani et al (2009Ghazouani et al ( , 2012 concluded that irrigation systems managed by the community were facing problems due to performance of the system.…”
Section: Introductionmentioning
confidence: 99%